2019
DOI: 10.1111/jzs.12334
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the “Chromodoris quadricolorgroup” of East Africa, with descriptions of two new species of the genusChromodorisAlder & Hancock, 1855 (Heterobranchia, Nudibranchia)

Abstract: The similarities and variations in nudibranch species of the "Chromodoris quadricolor group" (Heterobranchia, Nudibranchia) have historically created identification problems among both nudibranch enthusiasts and experts. In this study, we combine molecular genetic analyses using one nuclear gene (histone h3) and two mitochondrial genes (cytochrome c oxidase subunit I and ribosomal 16S RNA) with morphological data to ameliorate the identification of specimens from this complex in East Africa.We include a detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…1, Table 2). The species contained in the ten datasets that have relatively large values of µ m /µ n exclusively represent members of single genera that have radiated recently [15][16][17][18][19][20][21][22][23]. For example, the Conus dataset that represents an outlier ( µ m /µ n = 56.7) includes 44 members of the Cape Verde species flock, a group of species that may have radiated explosively during the past few million years [15,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…1, Table 2). The species contained in the ten datasets that have relatively large values of µ m /µ n exclusively represent members of single genera that have radiated recently [15][16][17][18][19][20][21][22][23]. For example, the Conus dataset that represents an outlier ( µ m /µ n = 56.7) includes 44 members of the Cape Verde species flock, a group of species that may have radiated explosively during the past few million years [15,24,25].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, 22 species of Chromodoris were recognized and Layton et al (2018) found 39 species lineages. Tibiriçá et al (2020) found 7 distinct lineages of Chromodoris present in East Africa, including one not found by Layton et al (2018). Bonomo & Gosliner (2020) sequenced additional specimens and found 44 distinct species lineages in Chromodoris, indicating that even more hidden diversity is found in the genus.…”
Section: Discussionmentioning
confidence: 80%
“…Perhaps the most surprising result was the recent work by Layton et al (2018) on Indo-Pacific species of Chromodoris. Subsequently, Tibiriçá et al (2020) described an additional two new species of Chromodoris from East Africa, C. celinae Tibiriçá, Pola, Ortigosa &Cervera, 2020 andC. helium Tibiriçá, Pola, Ortigosa &Cervera, 2020. Chromodoris is the most well-studied genus within the family and Layton et al (2018) recognized 17 new species, of which 5 were found from the Philippines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several lineages of heterobranch sea slugs contain multiple morphological conserved taxaoften pantropical found across ocean basins. These include sea hares (e. g., the Dolabrifera dolabrifera (Rang, 1828), Bursatella leachii Blainville, 1817, and Aplysia parvula M€ orch, 1863 species complexes; Vald es et al, 2018; Golestani et al, 2019;Bazzicalupo et al, 2020) but also sacoglossans (e. g., the Elysia ornata (Swainson, 1840) species complex; Krug et al, 2013;), cephalaspideans (e. g., the Chelidonura hirundinina (Quoy & Gaimard, 1833) species complex; Zamora-Silva & , and nudibranchs (e. g., Chromodoris quadricolor (R€ uppell & Leuckart, 1830) group;Tibiriç a et al, 2020). Due to the difficulties taxonomists have encountered identifying morphological differences between individuals from different ocean basins, most of these taxa have beenand some still areregarded as widely distributed species with disjunct ranges.…”
Section: Introductionmentioning
confidence: 99%